Combining Kidney Organoids and Genome Editing Technologies for a Better Understanding of Physiopathological Mechanisms of Renal Diseases: State of the Art - Steichen, Clara; Giraud, Sébastien; Hauet, Thierry (Frontiers in Medicine, 2020)
Kidney organoids derived from pluripotent stem cells became a real alternative to the use of in vitro cellular models or in vivo animal models. Indeed, the comprehension of the key steps involved during kidney embryonic development led to the establishment of protocols enabling the differentiation of pluripotent stem cells into highly complex and organized structures, composed of various renal cell types. These organoids are linked with one major application based on iPSC technology advantage: the possibility to control iPSC genome, by selecting patients with specific disease or by genome editing tools such as CRISPR/Cas9 system. This allows the generation of kidney organoïds which recapitulate important physiopathological mechanisms such as cyste formation in renal polycystic disease for example. This review will focus on studies combining these both cutting edge technologies i.e kidney organoid differentiation and genome editing and will describe what are the main advances performed in the comprehension of physiopathological mechanisms of renal diseases, as well as discuss remaining technical barriers and perspectives in the field.